Hospital Management: The Case of the District Referral Hospital Center of Moramanga - Hortense Haingovololona Ranaivoarison; Niaina Zakaria Rodolphe Andriamifidison; Ravaka Niaina Sabrina Andriamiarisoa; Voahanginirina Ramanantsoa; Mamy Jean Jacques Razafimahatratra; Fidiniaina Mamy Randriatsarafara (European Scientific Journal, ESJ, 2026)
Background: Hospital management remains a major challenge for ensuring quality care in a context marked by multiple health issues. This study aimed to identify the components of hospital management and assess the practices and approaches implemented at the District Referral Hospital Center (DRHC) of Moramanga.Methods: An evaluative, descriptive, cross-sectional study with a mixed-methods approach was conducted using retrospective data from 2022 to 2024. All staff members with at least six months of seniority were included. Data were collected through standards-based assessment grids and staff interviews, then analyzed according to the Donabedian model, focusing on structure, process, and outcomes of care.Results: Results showed a very high budget execution rate of approximately 99.5% over the study period, reflecting effective resource management despite a slight decline. Equipment coverage was satisfactory overall, reaching 80.94%. Reception and patient intake services were adequately organized, with six of eight required standards available, including triage systems, dedicated staff, and structured reception areas. Hospital activity trends revealed a marked increase in outpatient consultations in 2023, followed by a slight decline in 2024. Efficiency indicators showed a stable average length of stay of around 2.4 days, while the bed occupancy rate slightly decreased from 20.6 in 2022 to 19 in 2023. The hospital utilization rate also progressively declined from 0.8% to 0.52%.Conclusion: The need to strengthen medical staffing and increase revenue through investments, particularly by creating improved inpatient accommodation conditions, is evident in order to improve the quality of care and hospital performance, while taking into account the specific needs of patients and staff.